(untitled) (Journal of Forest and Livelihood, 2003)
The Federation of Community Forestry Users-Nepal has become the largest civil society organization not only in the forestry sector, but also in the country. This paper discusses the achievements of FECOFUN as a civil society organization and examines the way in which it has represented the interests of common forest users, and in particular, the poor and marginalized. It briefly discusses the major activities of FECOFUN aimed at advancing its interests at both national and local levels. It raises some issues as regards the ways in which it represents the common forest users, its governing structure and the resources it depends upon. This paper concludes that it is vital to review FECOFUN’s current policies, strategies and activities in order to better represent the interests of the poor and disadvantaged sections of society.